Prospective mechanism of action of the tubulysin synthetic derivative (TAM 1344) in HCT116 colon cancer cell line - Aisha Alqarni; Yasser A. Elnakady; Lamya Alsadhan; Muhammad Abbas; Wolfgang Richter; Badr A. Aldahmash; Mansour I. Almansour; Layali M. Almutairi; Ahmed Rady (Journal of King Saud University: Science, 2023)
Tubulin is still a highly valued target in cancer chemotherapy. Agents that target tubulin and microtubule dynamic are considered to be of high therapeutic potential. We conducted a study to assess the effects of TAM1344, a synthetic cytolysin that is derived from the natural tubulysins on the proliferation of cancer cell lines. Tubulysins are a group of naturally occurring cytotoxic compounds that are produced by Myxobacteria. Our results show that TAM1344 exhibit strong antiproliferative activity against different cancer cell lines at low nanomolar concentration. The measured IC50 values in HCT116, A549 and MCF7 cancer cell lines were 0.14 nM, 0.24 nM & 0.09 nM, respectively. In a direct comparison, the three cell lines were more sensitive to the drugs than the myxobacterial natural products tubulysin-A and –B. Additionally, in HCT116 cells, TAM1344 induces destabilization and depletion of the interphase microtubules as indicated by Immunofluorescence staining. Furthermore, the spindle pools of dividing cells show unusual, condensed phenotyping, a characteristic phenotype of many anti-tubulin agents. The nuclei of treated cells look fragmented in comparison to control cells, as detected with DAPI or PI staining. Furthermore, at low concentrations, TAM1344 induces an accumulation of the cells in the G2/M phase of the cell cycle, and therefore apoptotic induction, as indicated with flow cytometry analysis. In addition, it provoked an apoptotic process, marked by elevated caspase-3 activity. To conclude, the results indicate that TAM1344 is a novel, highly effective microtubule-targeting agent.